A high selectivity planar filtering quasi‐Yagi antenna. Issue 5 (13th January 2022) - Yuan, Hang; Chen, Fu‐Chang
Abstract: A high selectivity planar filtering quasi‐Yagi antenna employing the codesign of bandpass filter (BPF) and antenna is investigated in this article. A stub‐loaded resonator (SLR) and a half‐wavelength resonator are utilized as the feeding network to excite the driven dipole of the quasi‐Yagi antenna. The length of the driven dipole is about half‐wavelength, which can be equivalent to the last stage resonator of BPF, achieving a good filtering gain response. To improve the frequency selectivity, an elaborate balun structure is utilized, and a transmission zero (TZ) on the lower side of the passband is acquired. Together with the TZ introduced by the SLR at the upper edge, the antenna can achieve a sharp band‐skirt. An antenna prototype is fabricated and measured, showing a wide bandwidth up to 19.1% (from 3.1 to 3.76 GHz) with a flat gain response in band, an antenna peak gain of 4.85 dBi and a peak efficiency of −0.6 dB.